Teacher Training: An Opportunity for Transformation from Scientific Research - Caicedo Guevara, Beatriz Lorena (2024)
The essay aims to analyze the contributions of scientific research in teacher training and its impact on the transformation of education. At the University and in training centers, the curriculum that guides teachers has the task of not only updating the contents under cutting-edge demands, but it also has the fundamental task of adapting to the contextual realities of their work scenarios. In higher education, scientific research is the resource that guarantees the transformation of education professionals, their own students, and their communities. Examples of this are the Political Constitution of 1991, Law 115 of 1994 and Decree 1330 of 2019 (Colombia), which explain the importance and management of providing teachers with professional or continuous training in accordance with scientific processes. From this perspective, new contributions are made to the topic, taking teacher training to the construction of democratic scenarios, to the transformation of territories, systems, educational practices, curricular action, experience, and to society from a critical stance that transcends the discussion of knowledge.